Project-Based Practical on Students Creativity in the Control System Subject at Vocational School - Mirnawati Mirnawati; Ummiati Rahmah; Edy Sabara (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The low level of student creativity in engineering subjects is frequently attributed to monotonous instructional methods, whereas the demands of Industry 4.0 require vocational students to possess high creative competencies to manage complex control systems. This study aims to analyze the effect of project-based practicum implementation on student creativity in the Control Systems subject at Vocational School 5 Makassar. Employing a quantitative approach with a quasi-experimental pretest-posttest control group design, the research involved 44 grade XI students selected through random sampling, divided into experimental (n=23) and control (n=21) groups. Data was collected using a creativity questionnaire covering fluency, flexibility, originality, and elaboration dimensions. Statistical analysis, including Shapiro-Wilk's and Levene’s tests, preceded the hypothesis testing via independent samples t-test. The findings reveal that the experimental group achieved a posttest mean score ( ) of 81.48, significantly outperforming the control group’s score of 65.05. The t-test yielded a significant value of p = 0.000 (p < 0.05), confirming that project-based practicum acts as an effective catalyst in transforming creative potential into applicable innovative competencies. These results align with the vision of Competency-Based Training (CBT), providing a robust reference for vocational educators to implement innovative learning strategies relevant to the modern industrial landscape.